Os efeitos agudos da ingestão de Tereré (ilex paraguariensis) sobre indicadores de hidratação em judocas - FELIPE ELIEZER FERREIRA DENARDE (2023)
Introduction: Yerba mate (YM) (Ilex paraguariensis), consumed with cold water, that is, ‘tereré’, contains chemical compounds (e.g., caffeine, polyphenols, and saponins) which present vasodilating, moisturizing, and stimulating properties that could help athletes, especially those involved in fight modalities, who often experience fatigue and dehydration as a result of high intensity/duration training/competitions, wearing a kimono, and rapid weight loss strategies. However, in our review, we did not find studies involving yerba mate and hydration of athletes. Objective: To evaluate the acute effects of tereré (yerba mate) ingestion on hydration indicators in judokas. Methodology: This is a randomized, single-blind, crossover study (already approved by the Research Ethics Committee) involving 9 judokas (5 men and 4 women, 18 ± 2.71 years), healthy, experienced, and members of the sport federation (10.11 ± 3.05 years). Hydration was assessed using measurements of body weight, total body water, intra- and extracellular water (by electrical bioimpedance), thirst scale and sensation, and urine specific gravity. Measurements were taken before (M1 - 0 minute) and 60 minutes after (M2 - 80 minutes) ingestion of tereré (50g of herb with cold water 6mL/kg) or cold water (6mL/kg), and immediately after a judo training session (M3 ~181 min). Results: The two-way ANOVA test for repeated measures did not show a significant effect of group × time interaction (p > 0.05) for any outcome analyzed. The thirst sensation and scale increased significantly after the training session, but without differences between groups (p > 0.05). Conclusion: Our findings suggest that the acute ingestion of ‘tereré’ (Ilex paraguariensis) was as effective as water to promote hydration in judokas.